Health Security Challenges and their Economic and Developmental Impacts Applying to the Corona Pandemic - Abdul Qadir, Fatima Syed (The Arab Journal of Administration, 2024)
The World Health Organization has emphasized the right of every individual to ensure his health security by providing him with a health service at an appropriate cost, and by providing preventive medicine by providing vaccines and serums that help the immune system to resist diseases, and by providing medicine, clean water, and clean air. And healthy food free of preservatives, pesticides, and other pollutants. That the world faces every day challenges that weaken its health security, and cause an imbalance in its components, and this negatively affects the health of the individual, who is considered the main factor in the production and development process. Emerging diseases that cause global epidemics are a clear challenge to the process of economic development, and this was evident in the Corona pandemic, which left a global health crisis that had a major impact on production devices and economic activities in the whole world, and with the succession of viral waves and the continuation of precautionary measures The world has gone through an economic recession that went beyond what happened in the Great Depression of 1929. Therefore, efforts joined forces, and all countries of the world agreed to restore economic activity, and open outlets, universities, schools, and factories, until the global economy began to gradually resume production and activity, but with caution and the continuation of precautionary measures.